Bovine γ‐globulin, lactoferrin, and lactoperoxidase are relevant bovine milk allergens in patients with α‐Gal syndrome. Issue 12 (16th May 2021) - Perusko, Marija; Apostolovic, Danijela; Kiewiet, Mensiena Berentje Geertje; Grundström, Jeanette; Hamsten, Carl; Starkhammar, Maria; Cirkovic Velickovic, Tanja; van Hage, Marianne
Abstract: Background: Mammalian meat is the most common trigger of the allergic reactions in patients with α‐Gal syndrome (AGS). Milk and dairy, although less often, also cause a significant number of allergic manifestations. The aim of this study was to identify α‐Gal‐containing bovine milk proteins with allergenic properties among AGS patients. Methods: Thirty‐eight AGS patients with IgE to milk were included in the study. Milk proteins were analyzed for the presence of α‐Gal and for binding by patients' IgE using immunoblot, ImmunoCAP, and inhibition ELISA. Allergenicity of milk and milk proteins was assessed by basophil activation test. Results: More than half of the AGS patients reported allergic reactions to milk or dairy products. Bovine γ‐globulin (BGG), lactoferrin (LF), and lactoperoxidase (LPO) were identified as α‐Gal carrying proteins which were recognized by AGS patients' IgE. Whey mirrored the anti‐α‐Gal and IgE reactivity of BGG, LF, and LPO. Eighty‐nine percent of the patients displayed IgE to BGG, 91% to LF, and 57% to LPO. Inhibition of α‐Gal‐specific IgE binding was achieved by BGG, LF, LPO, and whey. These proteins also activated AGS patients' basophils. Interestingly, at lower concentrations, LF was the most potent inhibitor of IgE binding, and the most potent activator of basophils. Conclusion: BGG, LF, and LPO were all found to be relevant milk α‐Gal‐containing glycoproteins that bound AGS patients' IgE antibodies and activated their basophils. These proteins are probably involved in the allergic reactions to milk in AGS patients. LPO was for the first time shown to be an allergen. Abstract : More than half of the AGS patients reported allergic reactions to milk or dairy products. Bovine γ‐globulin, lactoferrin, and lactoperoxidase were found to be relevant milk α‐Gal‐containing glycoproteins that bound AGS patients' IgE antibodies and activated their basophils. These proteins are probably involved in the allergic reactions to milk and dairy products in AGS patients. Abbreviations: α‐Gal, galactose‐α‐1, 3‐galactose; AGS, α‐Gal syndrome; kUA /L, kilo units of allergen‐specific IgE per liter.